Answer:
y = - 3x + 9 or (y - 6) = - 3(x - 1)
Step-by-step explanation:
I'm assuming you are looking for the equation of the line.
First, let's find the slope of the line, which we use equation (y1-y2) / (x1-x2)
x1: 1 x2: 2
y1: 6 y2: 3
(6-3) / (1-2) = 3 / -1 = -3
The slope of the line is -3.
The equation for slope-intercept form is y = mx + b, where m is slope and b is the y - intercept.
y = -3x+b
Now substitute a set of points in (any coordinates work). I'll use (1, 6)
6 = -3(1)+b
6 = - 3 + b
b = 9
So our equation in slope intercept form is y = - 3x + 9
You can also write this in point slope form, (y-y1) = m (x-x1) m is still slope
(y - 6) = - 3(x - 1)